BERDAQ RUWXÍY MIYRASÍNIŃ ShAXS TÁRBIYASÍNDAǴÍ ORNÍ - Ernazarova, S.K. (SCIENCE and SOCIETY, 2026)
The article analyzes the role of the spiritual heritage of the famous representative of Karakalpak classical literature of the 19th century, the great poet and thinker, historian and bakhshi Berdakh Gargabay uly, in the upbringing of the individual. Berdakh created famous works in the philosophical-moral-pedagogical, literary-didactic direction. The article examines the ideas and socio-philosophical views put forward by the poet in his works, revealing the importance of his role in the upbringing of the individual of today.